2022
DOI: 10.1186/s13045-022-01238-y
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms and cancers: the intrinsic links and therapeutic potentials

Abstract: The circadian rhythm is an evolutionarily conserved time-keeping system that comprises a wide variety of processes including sleep–wake cycles, eating–fasting cycles, and activity–rest cycles, coordinating the behavior and physiology of all organs for whole-body homeostasis. Acute disruption of circadian rhythm may lead to transient discomfort, whereas long-term irregular circadian rhythm will result in the dysfunction of the organism, therefore increasing the risks of numerous diseases especially cancers. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 441 publications
(394 reference statements)
0
38
0
3
Order By: Relevance
“…Accumulating evidence shows that about 10% of the human genome is influenced by the circadian clock genes (CCGs) [11][12][13]. Accumulating evidence supports the relationship between incidence of malignancy and chronic circadian clock [14][15][16]. For example, studies have revealed that night shift work, including long-term shift work increase breast or prostate cancer risk [17,18].…”
Section: Ivyspringmentioning
confidence: 99%
“…Accumulating evidence shows that about 10% of the human genome is influenced by the circadian clock genes (CCGs) [11][12][13]. Accumulating evidence supports the relationship between incidence of malignancy and chronic circadian clock [14][15][16]. For example, studies have revealed that night shift work, including long-term shift work increase breast or prostate cancer risk [17,18].…”
Section: Ivyspringmentioning
confidence: 99%
“…Епіфіз є складовою частиною фотонейроендокринної системи. Саме тому фізіологічний контроль його ендокринної функції здійснюється світловим режимом навколишнього середовища [47,49,74]. У інтактних щурів шишкоподібна залоза оточена м'якою павутинною оболонкою, а безпосередньо до його поверхні щільно прилягає судинна оболонка.…”
Section: морфологічні зміни епіфізу при світловому десинхронозіunclassified
“…Застосування епіфізарного гормону пригнічує канцерогенез у тварин як при звичайному світловому режимі, так і при постійному освітленні [69,74]. На системному рівні мелатонін знижує продукцію гормонів, які сприяють старінню і раку, стимулює імунну систему, попереджає розвиток метаболічного синдро-му [67].…”
Section: функціональний стан організму при гіпомелатонінеміїunclassified
See 1 more Smart Citation
“…In the pathogenesis of colorectal cancer and oral squamous cell carcinoma, eATP mediated cancer cell migration and invasion by the signalregulated kinase and inflammatory protein [21][22][23][24]. The occurrence of cancer is increasingly demonstrated to associate with the chronic disruption of circadian clock [25]. eATP is rapidly hydrolyzed as short-term neurotransmitter in neuromodulation, secretion, and neurotransmission, and plays a role of long-term signaling molecule in cell differentiation, proliferation, and death [26].…”
Section: Introductionmentioning
confidence: 99%